Non-Perforating Ocular Trauma - Rieuwpassa, Marielo C.A; Yunita, Yunita; Pirade, Suryana R (Journal of Case Reports in Dental Medicine, 2022)
Introduction: Ocular trauma is trauma or injury that occurs to the eye that can cause damage to the eyeball, eyelids, eye nerves and orbital cavity, this damage will cause complications so that it interferes with the function of the eye as a sense of sightMethods: This case presents a 19 years old man who referred from Grestelina Hospital to Wahidin Sudirohusodo Hospital with complaints of pain in his right eye after being hit by a soda bottle cap. The patient opened the soda lid with his hand on the edge of the table and the bottle cap bounced off and hit the patient's right eye. The patient's eyes bleed and his vision becomes blurred. Physical examination revealed oculi dextra palpebral edema and conjunctiva hyperemic with normal visus 20/20. Furthermore Slit Lamp on the right eyeball showed palpebral edema, conjunctiva hyperemia; conjunctiva laceration at 4 o'clock is seen in the inferior nasal triangular shape with a size of 3x4 mm. Clear cornea with normal BMD.Result: This patient was diagnosed based on history, physical examination and inspectionConclusion: The diagnosis of perforating and non-perforating ocular trauma can be established based on the history, inspections and physical examination